The Consequences of Industrialization: Evidence from Water Pollution and Digestive Cancers in China - Ebenstein, Avraham (The Review of Economics and Statistics, 2012)
China's rapid industrialization has led to a severe deterioration in water quality in the country's lakes and rivers. By exploiting variation in pollution across China's river basins, I estimate that a deterioration of water quality by a single grade (on a six-grade scale) increases the digestive cancer death rate by 9.7%. The analysis rules out other potential explanations such as smoking rates, dietary patterns, and air pollution. I estimate that doubling China's levy rates for wastewater dumping would save roughly 17,000 lives per year but require an additional [dollar]500 million in annual spending on wastewater treatment.